The socioeconomic impact of armed conflict on Sudanese urban households: Evidence from a National Urban Household Survey - Kirui, Oliver K.; Ahmed, Mosab O. M.; Siddig, Khalid; Abushama, Hala; Intini, Vito; AlAzzawi, Shireen; Adam, Saef Alnasr; Terefe, Fekadu; Fallaha, Hasan; Merouani, Walid; Durrani, Akbar; Nohra, Nada (International Food Policy Research Institute, 2024)
Eighteen months of war have deeply affected urban households in Sudan: 31 percent have been displaced, full-time employment has plummeted by half, over 70 percent of the urban households in Sudan had all or some of school-aged kids stop attending school, and only one out of seven urban households can access full health services—concluded a new joint study from the United Nations Development Programme (UNDP) and the International Food Policy Research Institute (IFPRI), launched today.